The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4025/actascibiolsci.v42i1.51881
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening of extracts from Spiranthera odoratissima A. St.-Hil. (Rutaceae) leaves and their in vitro antioxidant and anti-Listeria monocytogenes activities

Abstract: Spiranthera odoratissima A. St.-Hil (Rutaceae), a shrub whose common name is manacá do Cerrado in Brazilian Portuguese, is about 1-m high and has been used by folk medicine to treat stomachache, kidney and liver infections, headache, rheumatism and as a blood purifier. This study aimed at preparing hexane, ethyl acetate, methanolic, hydroethanolic and aqueous extracts from S. odoratissima leaves, at carrying out preliminary phytochemical screening and at evaluating their in vitro antioxidant and anti-Listeria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…The above finding was in line with the research report by Irobi et al [ 17 ] whose analysis of this plant showed the presence of carbohydrates, alkaloids, saponins, fixed oil, and phytosterols. The above finding was still in concurrent with the study report carried out by Souza et al [ 18 ] whose analysis of Spiranthera odoratissima showed the presence of organic acids, reducing sugars, flavonoids, saponin compounds, coumarin compounds, phenolics, tannins, purine compounds, catechins, flavonol derivatives, sesquiterpene lactones, and anthraquinones. This shows that the phytochemicals from the studied plants leaves extracts had contributed to their antimicrobial activity against the tested clinically isolated dermatomycotic fungi.…”
Section: Discussionsupporting
confidence: 83%
“…The above finding was in line with the research report by Irobi et al [ 17 ] whose analysis of this plant showed the presence of carbohydrates, alkaloids, saponins, fixed oil, and phytosterols. The above finding was still in concurrent with the study report carried out by Souza et al [ 18 ] whose analysis of Spiranthera odoratissima showed the presence of organic acids, reducing sugars, flavonoids, saponin compounds, coumarin compounds, phenolics, tannins, purine compounds, catechins, flavonol derivatives, sesquiterpene lactones, and anthraquinones. This shows that the phytochemicals from the studied plants leaves extracts had contributed to their antimicrobial activity against the tested clinically isolated dermatomycotic fungi.…”
Section: Discussionsupporting
confidence: 83%
“…Os óleos essenciais ou óleorresinas são considerados ativos biológicos que apresentam compostos com atividades antimicrobianas (Cui et al, 2019;Cui et al, 2020;Souza et al, 2020). Controlar microrganismos patogênicos, como as bactérias, que são contaminantes indesejáveis que afetam diretamente os humanos é uma necessidade de saúde pública (DRUMOND et al, 2018).…”
Section: Introductionunclassified
“…Medicinal plants are less or non-toxic drug resources that are easily accessible, economical, and safe (Fathi, Ghane, & Pishkar, 2022). For many centuries, the treatment with these plants was the only resource available to various ethnic groups, and currently, plants continue to be frequently used for the treatment of pathologies in many countries (Gasparetto, Martins, Hayashi, Otuky, & Pontarolo, 2011;Souza et al, 2020), including Brazil. Besides being part of the culture, their use can be influenced by the high cost of medicines, the difficulty of access to medical consultations (Oliveira, Bovini, Bortoluzzi, Boff, & Boff, 2019), and the growing trend of the return of the use of natural resources as an alternative to synthetic medicines (Liu, Wang, & Kang, 2022).…”
Section: Introductionmentioning
confidence: 99%